Frameworks to identify best practices at the organization level: An analysis - Angulo Cuentas, Gerardo Luís; Camacho Pico, Jaime Alberto; Jaime Arias, Astrid (Journal of Business Economics and Management, 2015)
This paper identifies and analyzes the existing frameworks for supporting the identification and classification of best practices at an organization level.The major contribution of this paper is the proposition and application of three criteria for analyzing, comparing and classifying the four identified frameworks. The first criterion is based on structural complexity, facilitates defining the scope of initiatives to identify best practices. The second one, based on the framework orientation, permits choosing a framework depending of the type of studied processes. While the third criterion based on organizational levels, permits comparing and classifying the frameworks in terms of the strategic, tactic or operational issues.In conclusion are outlined important aspects in the selection of a framework according to two proposed scenarios: the best practices searching on Organizations of Excellence and the best practices searching on organizations with a similar business model.